Mycotoxins contamination in Brazilian coffee industry: the need of a One Health Approach - Viegas, Susana (2023)
Objective: This work aims to characterize mycotoxin contamination in two coffee industries from Brazil using as sampling methods settled dust and coffee beans. Methods: A total of 58 samples from the two coffee industries were assessed (20 settled dust, 20 filters used to vacuum the settled dust, and 18 coffee beans) and screened for mycotoxins presence. In all samples, 38 mycotoxins were analyzed by HPL-MS ((HPLC) Nexera (Shimadzu, Tokyo, Japan) with a mass spectrometry detector API 4000 (Sciex, Foster City, CA, USA). The mycotoxin concentration was calculated using external calibration. Results: In settled dust, all the samples showed contamination by at least one mycotoxin being the most reported mycophenolic acid and ochratoxin A. In addition, more three mycotoxins were detected namely: fumonisin B1, ochratoxin B, and zearalenone. Three (15%) samples showed contamination by three different mycotoxins and twelve (60%) by two mycotoxins. In the coffee beans samples, four mycotoxins were detected (aflatoxin B2, fumonisin B2, ochratoxin A, and mycophenolic acid) being the most reported mycophenolic acid with 4 samples (20%) presenting contamination by two different mycotoxins. Conclusions: The observed mycotoxin contamination highlights the need to consider this occupational environment as critical regarding occupational exposure to this risk factor. In addition, it also pinpoints a potential menace concerning food safety since mycotoxins are not degraded in the coffee processing treatments. Future research should include a One Health approach to tackle the different risks in this setting.